2017
DOI: 10.21608/epx.2017.16397
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and correlates of tobacco smoking among mentally ill male patients in El-Mamoura Psychiatric Hospital, Alexandria, Egypt

Abstract: Background: Despite widespread concern in public health regarding the increasing prevalence and burden of smoking and mental disorders, little is known about the double burden of these problems in Arab countries. Aim: To describe pattern and identify determinants of smoking among mentally ill male patients in El

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…[ 32 ] In an Egyptian study, the most common motives for smoking were habit (40.8%), sense of loneliness (31.1%), overcoming anxiety (28.6%), life stresses (28.2%), pressure from family and friends (12.7%), overcoming negative feelings (6.8%), and oppositional behavior (4.9%). [ 23 ] Similarly, stress, pleasure, peer and social pressure were the most common reasons for starting to smoke as revealed in an Iranian study. [ 33 ] Four basic motivational features of smokers' actions were in a Belgium paper: Smoking to increase a pleasant/positive effect, smoking to minimize a negative effect, smoking as a habit or with no attempt to mitigate/increase any effect, or smoking due to addiction.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[ 32 ] In an Egyptian study, the most common motives for smoking were habit (40.8%), sense of loneliness (31.1%), overcoming anxiety (28.6%), life stresses (28.2%), pressure from family and friends (12.7%), overcoming negative feelings (6.8%), and oppositional behavior (4.9%). [ 23 ] Similarly, stress, pleasure, peer and social pressure were the most common reasons for starting to smoke as revealed in an Iranian study. [ 33 ] Four basic motivational features of smokers' actions were in a Belgium paper: Smoking to increase a pleasant/positive effect, smoking to minimize a negative effect, smoking as a habit or with no attempt to mitigate/increase any effect, or smoking due to addiction.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to our findings, a study in El Mansoura reported high nicotine dependence in 58.2% of the study group, but moderate and low nicotine-dependent participants were 17.5% and 24.3% respectively. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation